Quality of information disclosed in annual reports of listed companies in the Czech Republic - David Čevela (European Financial and Accounting Journal, 2016)
This article examines the periodic information duty of the companies listed on Prague Stock Exchange in relation to the information disclosed within annual reports. The most significant regulatory requirements in force as at December 31, 2013 are identified and divided into several sub-areas - requirements on the financial statements, Report on relations and the Report of the Board of Directors, notes and complementary information and financial position and financial results. The identified requirements are then confronted with actual information disclosed within annual reports of the companies analysed to assess the compliance with the applicable law and IFRS. The main objective of the research is to evaluate the degree to which the listed entities comply with the reporting requirements set by the current legal framework by means of a content analysis using a predefined scoring system. The concluding section summarizes the main findings and suggests further possible research in this area.
Keywords: G18; 650; Disclosure quality; Periodic disclosure; Prague Stock Exchange